A novel zinc based binary catalytic system for CO2 utilization under mild conditions. Issue 2 (7th January 2016) - Desens, Willi; Kohrt, Christina; Spannenberg, Anke; Werner, Thomas
Abstract : A novel zinc based binary catalytic system for the synthesis of cyclic carbonates under mild and solvent-free conditions utilizing CO2 as a C1 building block is reported. Abstract : Herein we report the development of a novel binary catalytic system for the addition of CO2 to epoxides based on zinc iodide and an imidazolium salt. The influence of the nature of the imidazolium ion and the anion has been studied in a test reaction. The optimized system exhibits excellent activity and selectivity. Furthermore, the reaction can be performed under very mild (30 °C) and solvent free conditions yielding the desired cyclic carbonates in up to 99%.